Penghambatan Pertumbuhan Jamur Merang (Volvoriella Vovaceae) oleh Rhizopus sp pada Berbagai Media Biakan - Siti Hafsah; Alfizar Alfizar; Suci Zulinda (Jurnal Agrista, 2011)
Inhibited of Growth of Volvoriella volvaceae by Rhizopus sp some of cultivated mediaABSTRACT. The study was conducted in Dhampulo and Plant Protection Laboratory Agriculture Faculty of Syiah Kuala University during July to September 2011. The objective of the study were to know inhibited of growth of Volvoriella volvaceae by Rhizopus so all of cultivated media. The study was arranged in non factorial Randomized Completely Block design with six treatment and three replication. The treatments were straw media; cardboard box media; cane pulp media; sawdust media; water hyacinth media and fibrous shell. The result showed that Volvoriella volvaceae growth better on strow media than other media.